Um gênero EJA em Vitória, Espírito Santo : uma experiência em formação - Kilian, Rafael Bastos (2014)
This study aimed to follow the work and management processes of Elementary School Admardo Serafim de Oliveira (EMEF ASO), in Vitória, Espírito Santo. This school stands out from others by exclusively offering Adult and Youth Education (EJA) and by making it available in close proximity to the communities which it caters to, through the use of itinerant classes. In order to analyze the school’s work and management processes this research was based on the theoretical framework of the Activity Clinic and an institutional living ensued. This research sought to highlight the specifics of the work of EMEF ASO’s educators through the analysis schools documents and worker interviews and it suggests that the work an EJA educator constitutes a professional genre in its own rights, which differentiates itself from the professional genre of mainstream education.